Answer:
simplify x=0 is the correct answer
Step-by-step explanation:
the formula is too long so the link is below:
https://www.geteasysoloution.com/1/3x+12=x-4
Let
C---------> <span>the cost of a pizza
</span>t----------> <span>number of toppings
we know that
</span>$15.74-3t=$14.49-2t
15.74-14.49=3t-2t-------------> t=1.25
the cost of one topping is $1.25
and the cost of one pizza <span>without topping is
</span>15.74-3*1.25--------> $11.99
then
<span>an equation for the cost of a pizza, C, as a function of the number of toppings, t ordered is
</span>C=11.99+1.25t
the answer is
C=11.99+1.25t
Answer:
a = 10, b = 6, c = 2, d = 0
Step-by-step explanation:
Substitute the appropriate values of x into the equation and evaluate
x = - 3 : y = 4 - 2(- 3) = 4 + 6 = 10 → a
x = - 1 : y = 4 - 2(- 1) = 4 + 2 = 6 → b
x = 1 : y = 4 - 2(1) = 4 - 2 = 2 → c
x = 2 : y = 4 - 2(2) = 4 - 4 = 0 → d